Gestión del agua y conflictividad social en la cuenca del río Muga (Alt Empordá) - Ventura Pujolar, Montserrat; Ribas Palom, Anna; Saurí Pujol, David (Geographicalia, 2016)
In the last decades, the water managment in the Muga catchment has led into many territorial and social conflicts. These conflicts come from the intensive exploitation of the rich hydrological resources in a region where time ago the water users were not so diversified and the water demand was moderate. One time introduced the water availability and its users in the Muga catchment, this paper examines the driving forces of these water conflicts, the solution taken on and, finally, the probabilities of news conflicts in short medium term.
Keywords: Muga river; Alt Empordà; hydraulic planning; social conflict; social tension.